Outcome Assessment after Closed Reduction of Unilateral Mandibular Condylar Fractures - Nashrah Rehman Ansari, Shahzad Iqbal Malik, Shahid Ali, Muhammad Minam Qureshi, Muhammad Mustafa Ch, Muhammad Ali Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Condylar fractures are classified according to location and treatment planning depends on fracture type, age of patient and surgeons’ precedence. Closed reduction has been a common treatment, mainly for unilateral fractures, because it is noninvasive and eventually maintains viable mandibular function with less complications. Objective: To determine the outcome of closed reduction of mandibular condylar fractures in terms of mean change in mouth opening and occlusion. Material and Methods: The descriptive cross-sectional study was conducted in the Oral and Maxillofacial Surgery Department from October 2022 to March 2023. Total 80 Patients were included in the study. Preoperative X- rays PA Mandible and Orthopantomogram (OPG) were done to confirm the condylar fractures. Preoperative mouth opening could be recorded by a measuring scale as an interincisal distance between 11& 31 (FDI system). If these were missing, then 12 and 32(FDI system) were considered. Traumatic occlusions were recorded by photographs from front, right and left lateral after sufficient retraction. Patients included in the study were follow-up every week up to 4 weeks. After 4 weeks, elastics were removed. Post treatment mouth opening was recorded. Occlusion was recorded by photographs. Data was entered and analyzed on SPSS V 25. Results: Mean mouth opening pre-operatively and after 3 month post-operatively was 22.88±3.09mm. and 35.31±3.39mm. Mean change in mouth opening was 12.42±1.71mm. Among patients 56(70%) had good perceived occlusion. Patients whose perceived occlusion amongst them 18(75%) patients had moderate and 6(25%) had poor perceived occlusion. Conclusion: Results of this study demonstrate that mandibular condylar fractures can be treated effectively with closed reduction with better mouth opening and good occlusion respectively Keywords: Outcome, Closed reduction, Mandibular Condylar fractures, mean mouth opening and occlusion, mandibular fractures.